Ionospheric precursors of strong earthquakes observed using six GNSS stations data during continuous five years (2011–2015) - H.E. Eshkuvatov; B.J. Ahmedov; Y.A. Tillayev; M. Arslan Tariq; M. Ali Shah; Libo Liu (Geodesy and Geodynamics, 2023)
This study reports the morphological characteristics of anomalous variations in Global Navigation Satellite System Total Electron Content (GNSS-TEC) prior to the strong local earthquakes (EQ) that occurred during the period of 2011–2015. We have analyzed 20 earthquakes of magnitude M ≥ 5.6. A statistical technique is implemented on the data of six GNSS stations located in Tashkent, Kitab, and Maidanak in Uzbekistan, and Islamabad, Multan, Quetta in Pakistan. The results show continuous anomalous variations in TEC during 24 h before the occupancy of local earthquakes. It is shown that the precursors before the occurrence of strong earthquakes, in particular of magnitude 5.7, 7.7, 7.5, 7.8 and 7.3 are detected near Eastern Uzbekistan (26 May 2013), Southwestern Pakistan (24 September 2013), Hindukush region of Afghanistan (26 October 2015), and Central Nepal (25 April 2015) and (12 May 2015), respectively. The ionospheric anomalies appearing before the strong earthquakes at six GNSS stations are registered in 14 cases (70%) out of 20 selected EQs. It is depicted that anomalies referred to as ionospheric precursors appeared about 1–7 days prior to the occurrence of strong earthquakes.